2022
DOI: 10.3389/froh.2022.863723
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Benzyl Isothiocyanate on the Expression of Genes Encoding NADH Oxidase and Fibronectin-Binding Protein in Oral Streptococcal Biofilms

Abstract: Recent studies have shown that antimicrobial treatment results in up- or down regulation of several virulence-associated genes in bacterial biofilms. The genes encoding NADH oxidase (nox) and fibronectin-binding protein (fbp) are known to play important roles in biofilm growth of some oral bacterial species. The objective was to study the effect of benzyl isothiocyanate (BITC), an antimicrobial agent from Miswak plant, on the expression of nox and fbp genes in some oral streptococci. The biofilms were treated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Sofrata et al [43] reported a strong antibacterial efficacy of S. persica root chewing sticks against gram-negative oral pathogens due to the presence of benzyl isothiocyanate. Benzyl isothiocyanate, an active component of S. persica, is a well-known bactericidal material that can restrict acid production and the growth of many oral pathogens [44]. The presence of essential oils, sulfur, potassium chloride, sodium chloride, and some organic compounds contribute to its antimicrobial properties [45].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Sofrata et al [43] reported a strong antibacterial efficacy of S. persica root chewing sticks against gram-negative oral pathogens due to the presence of benzyl isothiocyanate. Benzyl isothiocyanate, an active component of S. persica, is a well-known bactericidal material that can restrict acid production and the growth of many oral pathogens [44]. The presence of essential oils, sulfur, potassium chloride, sodium chloride, and some organic compounds contribute to its antimicrobial properties [45].…”
Section: Antimicrobial Activitymentioning
confidence: 99%